The deconfinement phase transition in $Sp(2N)$ gauge theories and the density of states method - David Mason (Proceedings of The 40th International Symposium on Lattice Field Theory — PoS(LATTICE2023), 2023)
First-order phase transitions in the early universe might produce a detectable background ofgravitational waves. As these phase transitions can be generated by new physics, it is importantto quantify these effects. Many pure Yang-Mills gauge theories are known to undergo first-orderdeconfinement phase transitions, with properties that can be studied with lattice simulations.Despite the recent surge of interest in (2) gauge theories as a candidate for models of physicsbeyond the standard model, studies of these theories at finite temperature are still very limited. Inthis contribution we will present preliminary results of an ongoing numerical investigation of thethermodynamic properties of the deconfinement phase transition in (4) Yang-Mills theory, usingthe linear logarithmic relaxation algorithm. This method enables us to obtain a highly accuratedetermination of the density of states, allowing for a precise reconstruction of thermodynamicobservables. In particular, it gives access to otherwise difficult to determine quantities such asthe free energy of the system, even along metastable and unstable branches, hence providing anadditional direct observable to study the dynamics of the phase transition